Papillary thyroid carcinoma post total thyroidectomy: a case report - Darwito; Ardha, Doglas Rama Bayu; Sari, Ika Puspita; Ridhayani, Firda (Indonesian Journal of Pharmacology and Therapy, 2023)
Thyroid malignancies are considered rare but it is the most common type of endocrine malignancy that increase rapidly over the past decades. Specifically, papillary thyroid carcinoma (PTC) in the pyramidal lobe is extremely rare. Herein, we described a case of recurrence case of PTC in the pyramidal lobe post total thyroidectomy with category VI T2N1M1 (Bethesda classification) with right neck lymph nodes metastasis at once and attempt to determine both clinical presentation and therapeutical strategies to overcome this case to diminish the possibility of tumor recurrence and optimize therapeutic outcomes for PTC recurrence. It was reported a 28 yo female with a diagnosis of PTC from the pyramidal lobe post-total thyroidectomy procedure. A definite diagnosis of PTC is important to understand the patient's condition and as a consideration to decide the appropriate procedure to cure it. The management of PTC with total thyroidectomy followed by removing the possible root source of recurrent PTC, such as the pyramidal lobe, is mandatory to minimize the residual thyroid tissue that dan influenced PTC recurrent. Even though almost all PTC has an excellent prognosis, periodic follow-up after surgery, and patients’ adherence to their medication are still required.